2002
DOI: 10.1081/clt-120015836
|View full text |Cite
|
Sign up to set email alerts
|

Carbamazepine Poisoning: Elimination Kinetics and Quantitative Relationship with Carbamazepine 10,11-Epoxide

Abstract: Carbamazepine (amizepine) is a widely used psychotropic agent. A much easier accessibility of this drug, observed during the recent years, may account for an increasing number of acute intoxications with carbamazepine. The aim of this study was to determine the elimination kinetics of carbamazepine and its metabolite carbamazepine 10,11-epoxide, and to identify the quantitative relationship between concentrations of these compounds, in serum. The subjects were 41 patients with acute carbamazepine intoxication.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 8 publications
0
15
1
Order By: Relevance
“…Retrospective and observational studies suggest that the reference ranges for CBZ and CBZE are 4-12 mg/L and 0.8-3.2 mg/L, respectively [5,17] . The reference range has been a controversial concept, partly because it was initially defined on the basis of limited data for individual AEDs, which may not describe adequately the concentrationresponse relationship in patients with epilepsy [7] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Retrospective and observational studies suggest that the reference ranges for CBZ and CBZE are 4-12 mg/L and 0.8-3.2 mg/L, respectively [5,17] . The reference range has been a controversial concept, partly because it was initially defined on the basis of limited data for individual AEDs, which may not describe adequately the concentrationresponse relationship in patients with epilepsy [7] .…”
Section: Discussionmentioning
confidence: 99%
“…CBZE is thought to be partially responsible for the toxicity of CBZ treatment [3] . The poor rela-tionship between dose and blood levels and the high intraand inter-individual variability of those levels were observed in CBZ therapy [1,4,5] . In addition, CBZ treatment can be further complicated by concomitant use of other AEDs with induction and inhibition properties, which may have an impact on the pharmacokinetic profiles of both CBZ and CBZE [6] .…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have reported that the plasma levels of CBZ-10, 11-epoxide (CBZ-E), which is the main metabolite of CBZ, were very low and could be measured accurately only up to 72 h after a single dose of the parent drug (Eichelbaum et al, 1975;Winnicka et al, 2002). The plasma concentration of CBZ-E was too low to be measured following administration of the single dose used in the present study.…”
Section: Determination Of Cbz Plasma Concentrationsmentioning
confidence: 56%
“…Data for humans were adapted from those reported in the literature (Cotter et al, 1977;Kahela et al, 1983;Gérardin et al, 1990;Winnicka et al, 2002;Elqidra et al, 2004), while the data for dogs were obtained mainly from Kobayashi et al (2000) and Kou et al (2011). The main PK parameters of CBZ in species are compared in Table II.…”
Section: Comparison Of Pk and Bioavailabilities Among The Speciesmentioning
confidence: 99%
“…23 Elimination of carbamazepine would also have been delayed without intervention; in the setting of elevated serum concentrations, as seen in overdose, zero-order kinetics are observed (a fixed amount of drug is eliminated per unit of time). 24 To definitively demonstrate which modality (plasmapheresis or continuous venovenous hemodialysis) was most effective in eliminating carbamazepine from the patient would require measurement of carbamazepine concentration in the dialysate and pheresate. Our institution did not previously have laboratory protocols for this process; we have subsequently developed procedures for any future cases.…”
Section: Discussionmentioning
confidence: 99%